A 20 year review of acute and chronic gas and fat embolic lesions in ukstranded cetaceans: cetacean decompression sickness? - Jepson, Paul D.; Deaville, Rob; Bernaldo De Quirós Miranda, Yara; Patterson, Tony; Sierra Pulpillo, Eva María; Pocknell, Ann M.; Alves Godinho,Ana; Ross, Harry M.; Sacchini, Simona; Baker, John R.; Arbelo Hernández, Manuel Antonio; Reid, Robert J.; et al. (2011)
In the UK, 14/2774 stranded or by-caught cetaceans necropsied between 1990 and 2009 had acute or acute and chronic gas embolic lesions comprising 5/541 short-beaked common dolphins (Delphinus delphis), 5/31 Risso’s dolphins (Grampus griseus), 2/1729 harbour porpoises (Phocoena phocoena), 1/22 Sowerby’s beaked whales (Mesoplodon bidens) and 1/1 Blainville’s beaked whale (Mesoplodon densirostris). The most striking lesions in these cases were gas-filled fibrous cavitary lesions (0.2-6.0 cm diameter) in the liver in common dolphins (n=5), Risso’s dolphins (n=5), harbour porpoises (n=2) and the Blainville’s beaked whale and massive gas distension of the spleen in Risso’s dolphin (n=1). Histopathological examination showed acute lesions such as haemorrhage, fibrin thrombi and acute coagulative necrosis associated with intravascular gas bubbles (typically 50-750 μm diameter) and chronic lesions such as variable degrees of peri-cavitary fibrosis. Multiple mass stranding events (MSEs) predominantly involving beaked whales have been linked to naval exercises (using highintensity mid-frequency sonars). In Spain at least two sonar-induced MSEs had acute micro-haemorrhages in widely disseminated lipid-rich tissues and appearance of gas and fat emboli. Fat emboli were also determined in both UK and Spanish cases by Oil-Red-O and osmium post-fixation techniques. A type of cetacean decompression sickness (DCS) is the most likely pathogenetic mechanism for gas and fat emboli formation, possibly involving acoustically induced behavioural changes to dive profiles causing excessive nitrogen supersaturation on ascent. Acute and chronic gas and fat embolic lesions likely represent different stages of the same pathogenetic (DCS) mechanism and may share similar causal factors